RULES OF TRANSPORTATION OF GOODS AND PASSENGERS IN VEHICLES (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This article discusses the fundamental rules and regulations governing the transportation of goods and passengers in vehicles. It highlights the legal frameworks, safety standards, and best practices essential for ensuring efficient and secure transportation. The study examines the differences in regulations across various regions, focusing on compliance requirements and the implications of noncompliance. The article also addresses the technological advancements and innovations that enhance the transportation sector, promoting sustainability and reliability.